(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The development of disaster preparedness and emergency response competencies is one of the most important areas of education that all nursing students need to acquire because they will be on the front lines during a disaster. Therefore, this study investigated Nursing students' preparedness behavior, knowledge of disaster related terms, and their confidence to respond in emergencies. In addition, it examined the relationships between the three variables. Descriptive and correlational methods were used. Altogether 215 BSN students completed a written survey designed to collect data. The results indicated a high degree of BSN students' preparedness behavior (mean percent = 61.86%), primarily through receiving information about disasters. However, there were some low scores when students answered questions about their preparation for planning and having access to emergency telephone numbers. The BSN students had moderate knowledge regarding disaster preparedness (overall mean = 57.21%). These findings indicate that the students have limited knowledge about the specifics of what to do during a disaster. Although the BSN students stated they were confident in responding to emergencies (overall mean = 3.98), the correlation between their knowledge and confidence was not significantly related (r = .369). The implications of these findings suggest that confidence cannot be solely based on theory or knowledge; therefore, including hands-on practice, simulations, and drills should be included in the BSN program to develop both competency and readiness for disaster situations.